2001
DOI: 10.1016/s0008-6363(01)00323-6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins prevent cardiomyocyte apoptosis produced by norepinephrine infusion in ferrets

Abstract: NE administration at a dose which produced no significant increase in blood pressure or myocyte hypertrophy caused cardiomyocyte apoptosis in intact animals. This effect was associated with an increase in oxidative stress, up-regulation of Bax protein and down-regulation of Bcl-2 protein. Antioxidant vitamins prevented the changes produced by NE. The findings suggest that NE-induced myocyte apoptosis is mediated by oxidative stress, and that antioxidant vitamins may be beneficial in heart failure in which card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 62 publications
3
32
0
Order By: Relevance
“…Isoproterenol induces lipid peroxidation and norepinephrine increases hydroxyl free radicals and oxidized glutathione in animal hearts. [12][13][14] Therefore, adrenergic receptor blockers are useful for catecholamine-induced oxidative stress. Actually, Kukin et al 16 reported that not only carvedilol but also metoprolol, a ␤ 1 -selective blocker, reduced plasma lipid peroxidation in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isoproterenol induces lipid peroxidation and norepinephrine increases hydroxyl free radicals and oxidized glutathione in animal hearts. [12][13][14] Therefore, adrenergic receptor blockers are useful for catecholamine-induced oxidative stress. Actually, Kukin et al 16 reported that not only carvedilol but also metoprolol, a ␤ 1 -selective blocker, reduced plasma lipid peroxidation in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Experimental studies have shown the beneficial effects of antioxidants for prevention of heart failure. 5,14,32 However, the effectiveness of antioxidants for human patients with heart failure has not been clarified. Keith et al 33 reported that supplementation with vitamin E did not result in any significant improvement in patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theblocking effects of carvedilol may be important, because catecholamines such as isoproterenol or norepinephrine induce oxidative stress in the myocardium. 8,34,35 Other effects, such as anti-ischemic effects, including negative chronotropic effects via -receptors, and the direct antioxidative effect of carvedilol, may contribute to the reduction of oxidative stress. 8 Carvedilol reduced oxidative DNA damage with amelioration of heart failure, but only decreased the oxidative stress level by 19%.…”
Section: Circulation Journal Vol70 August 2006mentioning
confidence: 99%
“…22 Alternatively, -blockers inhibit the phosphorylation of PKA and decrease the cyclic AMP-mediated Ca 2+ 24 which induces hypertrophy 25 and apoptosis. 26 Antioxidants attenuate LV hypertrophy 27,28 and apoptosis. 29 LV hypertrophy and myocardial fibrosis caused by apoptosis increase the stiffness leading to diastolic dysfunction.…”
mentioning
confidence: 99%